EXPLORING COHESIVE DEVICES IN SEVENTH-GRADE ENGLISH TEXTBOOKS: A DISCOURSE ANALYSIS - Riska Nurul Fitriani; Aliva Rosdiana (Indonesian EFL Journal, 2025)
English textbooks serve as crucial instructional resources in Indonesian EFL contexts, with cohesive devices like conjunctions playing a vital role in text comprehension. Despite extensive research on cohesion, seventh-grade textbooks remain underexplored, particularly in Indonesia. This study analyzes conjunction types (additive, adversative, causal, temporal) and their functions in a seventh-grade English textbook to evaluate their role in enhancing coherence and pedagogical effectiveness. A qualitative descriptive approach was employed, examining 13 texts from "English for Grade VII" (Azari, 2013) using Halliday and Hasan’s (1976) cohesion framework. Data were coded manually, with inter-rater reliability (κ = 0.89) ensuring consistency. Additive conjunctions dominated (55%), facilitating idea elaboration, followed by temporal (25%), adversative (10%), and causal (10%) conjunctions. Additives maintained conversational flow ("and"), while temporals structured narratives ("after"). Adversatives ("but") and causals ("because") introduced contrast and logic at developmentally appropriate levels. The textbook effectively employs conjunctions to scaffold coherence, balancing simplicity and complexity for young learners. Its distribution aligns with research on cognitive load and cultural relevance. Textbook developers should maintain this conjunction balance while incorporating more diverse examples. Teachers can use these findings to design conjunction-focused exercises. Future studies should expand to multiple textbooks and longitudinal learning outcomes.